Recognizing ion ligand binding sites by SMO algorithm - Wang, Shan (BMC Mol Cell Biol, 2019)
BACKGROUND: In many important life activities, the execution of protein function depends on the interaction between proteins and ligands. As an important protein binding ligand, the identification of the binding site of the ion ligands plays an important role in the study of the protein function. RESULTS: In this study, four acid radical ion ligands (NO(2)(−),CO(3)(2−),SO(4)(2−),PO(4)(3−)) and ten metal ion ligands (Zn(2+),Cu(2+),Fe(2+),Fe(3+),Ca(2+),Mg(2+),Mn(2+),Na(+),K(+),Co(2+)) are selected as the research object, and the Sequential minimal optimization (SMO) algorithm based on sequence information was proposed, better prediction results were obtained by 5-fold cross validation. CONCLUSIONS: An efficient method for predicting ion ligand binding sites was presented.